Investigating the Organizational Resilience of Hospitals During Emergencies and Disasters: A Comprehensive Review of the Components - Seyghalani Talab, Fatemeh; Ahadinezhad, Bahman; Khosravizadeh, Omid (Health in emergencies and disasters quarterly, 2024)
Background: A hospital’s ability that is exposed to risk is important for maintaining its basic structure and functions by relying on increasing various capacities recovering from the effects of risks at the right time and reaching a higher level of readiness. Accordingly, the present study investigates the components of organizational resilience of hospitals during emergencies and disasters. Materials and Methods: This comprehensive review was conducted in 2022. Data was collected by searching keywords in PubMed, Web of Science, Science Direct, Magiran, Irandoc, and SID databases from 2012 to 2022. The quality of the articles was evaluated using the strengthening of the reporting of observational studies in the epidemiology checklist by two researchers. The results of the studies were categorized in the form of dimensions and components. Results: A total of 20 studies with various methods were summarized after quality assessment. Subsequently, the identified components were categorized into 5 dimensions as follows: the vulnerability of the hospital (18 components), preparedness (31 components), management and support (33 components), responsiveness and adaptability (35 components), and recovery after crisis (8 components). Conclusion: A review of the studies showed the importance of each component in the field of hospital organizational resilience. In this regard, policymakers at the decision-making level and managers at the executive level should pay attention to the components that affect the organizational resilience of the hospital regarding the structure, process, and expected consequences, and then make the necessary decisions regarding the implementation of policies and solutions.